Anakinra for palmoplantar pustulosis: results from a randomized, double‐blind, multicentre, two‐staged, adaptive placebo‐controlled trial (APRICOT). (1st February 2022) - Cro, S.; Cornelius, V.R.; Pink, A.E.; Wilson, R.; Pushpa‐Rajah, A.; Patel, P.; Abdul‐Wahab, A.; August, S.; Azad, J.; Becher, G.; Chapman, A.; Dunnill, G.; et al.
Summary: Background: Palmoplantar pustulosis (PPP) is a rare, debilitating, chronic inflammatory skin disease that affects the hands and feet. Clinical, immunological and genetic findings suggest a pathogenic role for interleukin (IL)‐1. Objectives: To determine whether anakinra (an IL‐1 receptor antagonist) delivers therapeutic benefit in PPP. Methods: This was a randomized (1 : 1), double‐blind, two‐staged, adaptive, UK multicentre, placebo‐controlled trial [ISCRTN13127147 (registered 1 August 2016); EudraCT number: 2015‐003600‐23 (registered 1 April 2016)]. Participants had a diagnosis of PPP (> 6 months) requiring systemic therapy. Treatment was 8 weeks of anakinra or placebo via daily, self‐administered subcutaneous injections. Primary outcome was the Palmoplantar Pustulosis Psoriasis Area and Severity Index (PPPASI) at 8 weeks. Results: A total of 374 patients were screened; 64 were enrolled (31 in the anakinra arm and 33 in the placebo arm) with a mean (SD) baseline PPPASI of 17·8 (10·5) and a PPP investigator's global assessment of severe (50%) or moderate (50%). The baseline adjusted mean difference in PPPASI favoured anakinra but did not demonstrate superiority in the intention‐to‐treat analysis [–1·65, 95% confidence interval (CI) –4·77 to 1·47; P = 0·30]. Similarly, secondary objective measures, including fresh pustule count (2·94, 95% CI –26·44 to 32·33; favouring anakinra), total pustule count (–30·08, 95% CI –83·20 to 23·05; favouring placebo) and patient‐reported outcomes, did not show superiority of anakinra. When modelling the impact of adherence, the PPPASI complier average causal effect for an individual who received ≥ 90% of the total treatment (48% in the anakinra group) was –3·80 (95% CI –10·76 to 3·16; P = 0·285). No serious adverse events occurred. Conclusions: No evidence for the superiority of anakinra was found. IL‐1 blockade is not a useful intervention for the treatment of PPP.